2015
DOI: 10.1016/j.crad.2015.06.083
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the response of gastric carcinomas to neoadjuvant chemotherapy using iodine concentration on spectral CT: a comparison with pathological regression

Abstract: Changes in the IC for gastric carcinomas following NC were detected using spectral CT and correlated with histopathological regression. The prediction efficacy for IC was better than that for tumour thickness, with IC on the arterial phase being a better predictor than IC on the venous phase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 23 publications
3
31
0
Order By: Relevance
“…Thus, the TIU is not affected by slight changes in the border. Our results are somewhat consistent with those of Tang et al, who showed that a change in the iodine concentration is related to the pathological regression of gastric cancer after neoadjuvant chemotherapy (Tang et al 2015). Specifically, they obtained their data on the bi-dimensional planes rather than in the three-dimensional (3D) mode that was examined in our study.…”
Section: Discussionsupporting
confidence: 82%
“…Thus, the TIU is not affected by slight changes in the border. Our results are somewhat consistent with those of Tang et al, who showed that a change in the iodine concentration is related to the pathological regression of gastric cancer after neoadjuvant chemotherapy (Tang et al 2015). Specifically, they obtained their data on the bi-dimensional planes rather than in the three-dimensional (3D) mode that was examined in our study.…”
Section: Discussionsupporting
confidence: 82%
“…Although Tang L et al [18] and Hu S et al [19] have demonstrated the value of spectral CT in evaluating the therapeutic effect of neoadjuvant chemotherapy on gastric carcinomas and 125 I interstitial brachytherapy on pancreatic carcinoma, the potential role of CT spectral imaging parameters as early predictors of tumour response after VTA treatments has not been previously well established in the literature. Dual-source dual-energy CT (DECT) has also been demonstrated to be effective in early prediction of tumour response in human study of Meyer M et al [43], however, this study has used the first available DECT scan instead of prior treatment similar to our study as baseline evaluation, which may lead to a long term evaluation bias.…”
Section: Discussionmentioning
confidence: 98%
“…Multiple studies have demonstrated the validity of iodine concentration quantification in material differentiation, material identification and tumour response after radiotherapy or chemotherapy [17][18][19][20][21]. CT spectral imaging parameters might be useful in repeated monitoring of the microenvironmental change of tumours after administration of antiangiogenic agents, because antiangiogenic agents would affect the tumour vasculature and result in necrosis of the tumour, causing the change of iodine concentration in tumours after iodinated contrast agent administration.…”
Section: Introductionmentioning
confidence: 99%
“…This IC value has been proven to show a strong correlation with the actual iodine concentration in the phantom[7]. Recently, preliminary studies have reported the use of the IC value to differentiate benign and malignant lesions, to find embolisms, and to evaluate the efficacy of anticancer therapy[8-11]. Particularly in the evaluation of neoadjuvant chemotherapy of GC, the IC value was proven to be a more robust imaging biomarker than the morphology index[11].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, preliminary studies have reported the use of the IC value to differentiate benign and malignant lesions, to find embolisms, and to evaluate the efficacy of anticancer therapy[8-11]. Particularly in the evaluation of neoadjuvant chemotherapy of GC, the IC value was proven to be a more robust imaging biomarker than the morphology index[11]. However, it was not clear how this correlated with radiological-pathological features.…”
Section: Introductionmentioning
confidence: 99%